Analytical model of the dynamic response of clamped metallic sandwich beam subjected to underwater impulsive loading. (January 2019) - Huang, Wei; Zhang, Wei; Li, Dacheng; Liu, Jiayi
Abstract: An analytical model is developed for the dynamic response of clamped metallic sandwich beam subjected to underwater impulsive loading. Considering the coupling interaction of different response stages, the theoretical dynamic response is achieved for the large deflection of metallic sandwich beams with a new yield criterion during the structural deformation stage. The computational and theoretical dynamic response of the sandwich beam are compared with the previous experimental results in terms of the response time, response rate, velocity of the faces, and transverse deflection. The results indicate that the tighter solution of transverse deflection from the new circumscribing and inscribing yield surfaces exhibits a good agreement with the experimental and numerical results, demonstrating that the analytical prediction is more accurate than the previous analytical model. The optimization shows that sandwich beams not always outperform the monolithic beams. The optimal sandwich beam designs are sensitive to the span of the beam and the longitudinal strength of the core. Highlights: An analytical model is presented to analyze the dynamic response of clamped metallic sandwich beams subjected to underwater impulsive loading. Coupling interaction of different response stages and a new yield criteria of metallic sandwich beams are considered in the analytical model. Comprehensive comparisons among the experiments, numerical simulations, and analytical solutions are carried out. The optimal design of sandwich beams is conducted by employing the analytical model.